Copyright Problems of Lasem Hand-drawn Batik as an Object of Fiduciary Guarantee in Rembang Regency - Kholifatul Aziz, Elfira Nur; Mashdurohatun, Anis (Jurnal Konstatering, 2025)
Abstract.This article aims to examine and analyze the implementation of copyright on Lasem batik tulis products as objects of fiduciary guarantees and the problems and solutions in the implementation of copyright on Lasem batik tulis products as objects of fiduciary guarantees in realizing the creative economy in Rembang Regency. This article is an empirical juridical legal research with the statue approach and historical approach methods. The data collection technique used is a field study in the form of observation and interviews as well as a literature study. The data analysis method used in analyzing the data is an interactive qualitative model analysis. The results of the study show that results of the research and study show that until now there has been no Banking or non-banking Institution that has implemented Intellectual Property such as copyright of Lasem batik artwork as an object of fiduciary guarantee or collateral. The non-implementation of intellectual property-based financing is due to several problems, namely regarding regulations, related Institutions or Officials, the concept of valuation and special Institutions for Intellectual Property valuation, the Copyright execution system as an object of fiduciary guarantee and for Creative Economy Actors. From the problems faced, there are solutions that can be done, including: 1) Renewal of regulations, 2) Increasing knowledge and understanding of related Institutions and officials, 3) Establishing a valuation system and special Institution to assess appropriate copyright, 4) Preparing a mechanism for executing Copyright as an appropriate and correct object of fiduciary guarantee and 5) increasing awareness of creative economy actors regarding the legal protection of Copyright.Keywords: Batik; Copyright; Fiduciary; Guarantee; Problems.